2014
DOI: 10.1016/j.fertnstert.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycosylated human chorionic gonadotropin as an early predictor of pregnancy outcomes after in vitro fertilization

Abstract: Objective To determine if hyperglycosylated hCG (hhCG), produced by invasive trophoblasts, measured as early as 9 days after egg retrieval can predict ongoing pregnancies (OP) after in vitro fertilization and fresh embryo transfer (IVF-ET). Design Cohort Setting Academic ART center Patients Consecutive patients undergoing IVF-ET Interventions Serum hhCG and hCG levels measured 9 (D9) and 16 (D16) days after egg retrieval Outcome Ongoing pregnancy (OP) beyond 9 weeks of gestation Results OP (62 of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…In natural conception cycles, hCG‐H comprised 88% of total serum hCG in continuing pregnancies but only 44% in failing pregnancies on the first day of hCG detection . In IVF/ICSI cohort, serum samples taken as early as 9–16 days after oocyte retrieval (around day 4–11 after embryo transfer) could discriminate between an ongoing pregnancy and a pregnancy which would result in a spontaneous abortion . Measurements of hCG‐H can also discriminate between ongoing pregnancies, spontaneous abortions and biochemical pregnancies within 2 weeks following embryo transfer .…”
Section: The Use Of Hcg‐h As a Biomarker: Potential Diagnostics Of Emmentioning
confidence: 99%
“…In natural conception cycles, hCG‐H comprised 88% of total serum hCG in continuing pregnancies but only 44% in failing pregnancies on the first day of hCG detection . In IVF/ICSI cohort, serum samples taken as early as 9–16 days after oocyte retrieval (around day 4–11 after embryo transfer) could discriminate between an ongoing pregnancy and a pregnancy which would result in a spontaneous abortion . Measurements of hCG‐H can also discriminate between ongoing pregnancies, spontaneous abortions and biochemical pregnancies within 2 weeks following embryo transfer .…”
Section: The Use Of Hcg‐h As a Biomarker: Potential Diagnostics Of Emmentioning
confidence: 99%
“…27 In another study with 46 patients following fresh day 3 or day 5 embryo transfers, median hCG-H levels were found to be significantly different at both 9 and 16 days following oocyte retrieval among ongoing and failed pregnancies (biochemical pregnancies and clinical pregnancy losses combined). 28 In this same study, using a retrospective cohort of 112 patients following fresh embryo transfer for confirmation, hCG-H >8165 pg/mL (8.2 ng/mL) 16 days after oocyte retrieval had a PPVof 96% for ongoing pregnancy and a NPV of 77%.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 88%
“…43 Serum hCG-H for prediction of pregnancy prognosis following IVF has also been explored to a limited extent, with hCG-H cut-offs of 6e8 ng/mL being reported to differentiate between ongoing and failed pregnancies. 27,28 In 1 study, a blinded prospective trial of serum hCG-H levels drawn in IVF patients 6 and 12 days after fresh day 3 or day 5 embryo transfers found that following blastocyst transfer (n ¼ 39), serum hCG-H 6 days (300 pg/mL) and 12 days ( >6000 pg/mL, or 6 ng/mL) after transfer predicted clinical pregnancy with a specificity of 100% and sensitivities of 92% and 88%, respectively. 27 In another study with 46 patients following fresh day 3 or day 5 embryo transfers, median hCG-H levels were found to be significantly different at both 9 and 16 days following oocyte retrieval among ongoing and failed pregnancies (biochemical pregnancies and clinical pregnancy losses combined).…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
See 1 more Smart Citation
“…Sandy Chuan, M.D,2014,said that, in patient undergoing assisted reproduction , hCG-H is detectable in maternal serum 9 days after egg retrieval IVF-ET cycle, so hCG-H was superior to traditional hCG and highly predictive of ongoing pregnancies (48) . Our study finding reported higher hCG-H level in molar pregnancy in comparison with normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%